Absolute Configuration and Chiroptical Properties of Flexible Drug Avapritinib - Ya-Dong Yang; Chen Zhao; Liang-Peng Li; Yi-Xin Lv; Bei-Bei Yang; Xin Li; Ru Wang; Li Li (Pharmaceuticals)
Background/Objective: Avapritinib is an orally bioavailable tyrosine kinase inhibitor and was approved by the FDA in 2020 for gastrointestinal stromal tumor treatments. Although avapritinib is known to be chiral, its stereochemistry was initially established randomly. This study aims to develop a definitive method for determining avapritinib’s absolute configuration and propose a universal methodology for stereochemical characterization of flexible chiral drugs. Methods: The absolute configuration of avapritinib was determined through an integrated approach combining chiral resolution, chiroptical spectroscopy and synthetic validation. Enantiomeric separation was achieved via chiral liquid chromatography, followed by comprehensive chiroptical characterization including electronic circular dichroism (ECD), specific optical rotation and optical rotatory dispersion. Conformational analysis and density functional theory (DFT) calculations correlated experimental spectra with theoretical predictions, facilitating definitive configurational assignment. The stereochemical determination were further verified through ECD derivatization and chemical synthesis. Finally, the enantiomers’ kinase inhibition profiles against c-KIT D816V were quantitatively assessed. Results: Two enantiomers of avapritinib were resolved via chiral HPLC and a Chiralpak IG column. Through combined experimental ECD spectra and time-dependent DFT calculations employing the core extraction method, the levo-isomer was unambiguously determined as S configuration. This stereochemical assignment was confirmed by p-cyanobenzaldehyde derivatization and de novo synthesis. Biological evaluation revealed (S)-(−)-avapritinib exhibited superior c-KIT D816V inhibitory activity compared to its (R)-(+)-counterpart, a finding corroborated by molecular docking studies elucidating their differential target interactions. Conclusions: This study advances avapritinib stereochemical understanding and establishes a definitive protocol for its absolute configuration assignment, serving as a paradigm for flexible chiral drug characterization.